Synthesis, Characterization, Anticancer, and Antioxidant Studies of Ru(III) Complexes of Monobasic Tridentate Schiff Bases - Ikechukwu P. Ejidike; Peter A. Ajibade (Bioinorganic Chemistry and Applications)
Mononuclear Ru(III) complexes of the type [Ru(LL)Cl2(H2O)] (LL = monobasic tridentate Schiff base anion: (1Z)-N′-(2-{(E)-[1-(2,4-dihydroxyphenyl)ethylidene]amino}ethyl)-N-phenylethanimidamide [DAE], 4-[(1E)-N-{2-[(Z)-(4-hydroxy-3-methoxybenzylidene)amino]ethyl}ethanimidoyl]benzene-1,3-diol [HME], 4-[(1E)-N-{2-[(Z)-(3,4-dimethoxybenzylidene)amino]ethyl}ethanimidoyl]benzene-1,3-diol [MBE], and N-(2-{(E)-[1-(2,4-dihydroxyphenyl)ethylidene]amino}ethyl)benzenecarboximidoyl chloride [DEE]) were synthesized and characterized using the microanalytical, conductivity measurements, electronic spectra, and FTIR spectroscopy. IR spectral studies confirmed that the ligands act as tridentate chelate coordinating the metal ion through the azomethine nitrogen and phenolic oxygen atom. An octahedral geometry has been proposed for all Ru(III)-Schiff base complexes. In vitro anticancer studies of the synthesized complexes against renal cancer cells (TK-10), melanoma cancer cells (UACC-62), and breast cancer cells (MCF-7) was investigated using the Sulforhodamine B assay. [Ru(DAE)Cl2(H2O)] showed the highest activity with IC50 valves of 3.57±1.09, 6.44±0.38, and 9.06±1.18 μM against MCF-7, UACC-62, and TK-10, respectively, order of activity being TK-10 < UACC-62 < MCF-7. The antioxidant activity by DPPH and ABTS inhibition assay was also examined. Scavenging ability of the complexes on DPPH radical can be ranked in the following order: [Ru(DEE)Cl2(H2O)] > [Ru(HME)Cl2(H2O)] > [Ru(DAE)Cl2(H2O)] > [Ru(MBE)Cl2(H2O)].